A Curatorial Model for Teaching Renaissance Book History in Canada - Jenstad, Janelle; Kelly, Erin E. (Renaissance and Reformation / Renaissance et Réforme, 2014)
Only by holding early printed books can students learn both the strangeness of the past and its oddly familiar struggle with technological innovation. Even partial collections like the one at the University of Victoria have enough rare books to serve these purposes. But how do we teach book culture and intellectual history when we do not have multiple or even representative books from many authors, countries, and sometimes whole decades? We adopt a curatorial teaching model that invites students to find, select, and chart a narrative through the materials that we do have. This article describes our curatorial projects in the hope that others will undertake similar endeavours. It also explains how the very partiality of our collection has generated wonderful opportunities for students to learn not just book history but also the history of Canadian universities, libraries, collectors, and Renaissance studies.